Drug-Induced Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Recreational drug-induced seizures in 47 patients seen at the San Francisco General Hospital between 1975 and 1987 were reported by the Division of Clinical Pharmacy and Department of Neurology, University of California, San Francisco, CA.